Treatment as prevention effect of direct-acting antivirals on primary hepatitis C virus incidence: findings from a multinational cohort between 2010 and 2019. (February 2023) - van Santen, Daniela K.; Sacks-Davis, Rachel; Stewart, Ashleigh; Boyd, Anders; Young, Jim; van der Valk, Marc; Smit, Colette; Rauch, Andri; Braun, Dominique L.; Jarrin, Inmaculada; Berenguer, Juan; Lazarus, Jeffrey V.; et al.
Summary: Background: Broad direct-acting antiviral (DAA) access may reduce hepatitis C virus (HCV) incidence through a "treatment as prevention" (TasP) effect. We assessed changes in primary HCV incidence following DAA access among people living with HIV (PLHIV). Methods: We used pooled individual-level data from six cohorts from the International Collaboration on Hepatitis C Elimination in HIV Cohorts (InCHEHC). Follow-up started from the first recorded negative HCV antibody test date and ended at last negative antibody test or estimated infection date. Follow-up was restricted to 2010–2019. We used segmented Poisson regression to model trends across pre-, limited- (i.e., restrictions on access) and broad-DAA access periods. Findings: Overall, 45, 942 participants had at least one HCV antibody negative result and follow-up between 2010 and 2019. We observed 2042 incident HCV infections over 248, 189 person-years (PY). Pooled incidence decreased from 0.91 per 100 PY in 2015 to 0.41 per 100 PY in 2019. Compared to the average pre-DAA period incidence (0.90 per 100 PY), average incidence was similar during the limited-DAA access period (Incidence rate ratio [IRR] = 0.98; 95%CI = 0.87, 1.11), and 52% lower during the broad-DAA access period (IRR = 0.48; 95%CI = 0.42, 0.52). The average annual decline in HCV incidence was 2% in the pre-DAA period; an additional 9% annual decline in incidence was observed during the limited-DAA access period (IRR = 0.91; 95%CI = 0.82, 1.00) and a further 20% decline in the broad-DAA access period (IRR = 0.80, 95%CI = 0.73, 0.89). Interpretation: Our findings suggest that broad DAA access has a TasP effect on primary HCV incidence among PLHIV. Based on the initial years of DAA availability, the countries in the InCHEHC collaboration are on track to meet the World Health Organization's 80% HCV incidence reduction target for PLHIV by 2030. Funding: This study was funded by the Australian Government National Health and Medical Research Council (Grant number GNT1132902 ).